2021
DOI: 10.3390/ijerph182111381
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Mental Health among International Students during the COVID-19 Pandemic in South Korea

Abstract: The purpose of this study was to investigate mental health problems among international students in South Korean universities during the COVID-19 pandemic, as well as to identify the factors that affect their mental health. A total of 488 international students living in South Korea participated in a web-based survey. The questionnaire was created using the Google Forms platform, and a link to the questionnaire was shared through social media. Multiple logistic regression analysis was conducted to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 42 publications
3
24
0
1
Order By: Relevance
“…In both their studies, Slovak students reported more depression than anxiety ( 33 , 34 ), which corresponds to the results of the presented study. A very similar prevalence of mental health problems such as anxiety and depression was found among college students from Saudi Arabia ( 39 ) and South Korea ( 40 ), while students from Brazil showed a higher prevalence of both depression and anxiety ( 41 ). In comparison with the results of this study, Duan et al ( 42 ) revealed a higher prevalence of depression but a lower prevalence of anxiety among Chinese college students.…”
Section: Discussionmentioning
confidence: 65%
“…In both their studies, Slovak students reported more depression than anxiety ( 33 , 34 ), which corresponds to the results of the presented study. A very similar prevalence of mental health problems such as anxiety and depression was found among college students from Saudi Arabia ( 39 ) and South Korea ( 40 ), while students from Brazil showed a higher prevalence of both depression and anxiety ( 41 ). In comparison with the results of this study, Duan et al ( 42 ) revealed a higher prevalence of depression but a lower prevalence of anxiety among Chinese college students.…”
Section: Discussionmentioning
confidence: 65%
“…(Brooks et al, 2020; Romeo et al, 2021). Females and international students have been suggested to be particularly vulnerable, though evidence of this is not consistent (Alam et al, 2021; Chen et al, 2020; Gestsdottir et al, 2021; Kim & Kim, 2021; Pappa et al, 2020; Prowse et al, 2021; J. Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to domestic students, international students were more vulnerable to mental health problems during the pandemic [ 18 , 20 ]. A study was conducted on international students of South Korean universities during the COVID-19 pandemic, which showed that the prevalence rates of sleep problems, anxiety, and depression among international students were 47.1%, 39.6%, and 49%, respectively [ 21 ]. Even under normal conditions, international students are more vulnerable to mental problems (e.g., depression), struggle with the local medical system, and are less inclined to seek psychological help [ 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%